(untitled) (Applied Biological Research, 2016)
Actinobacillosis is an infectious disease caused by a Gram-negative coccobacilli, Actinobacillus lignieresii, reported world widely often as affecting the soft tissues especially tongue of cattle and sheep (Dirksen et al., 2005; Radostits et al., 2007). A. lignieresii is a commensal of upper digestive tract of ruminants. Traumatic erosion, ulcer and penetrating lesion induced by hard fibrous feed causes a breach in skin barrier integrity and can establish an infection (Brown et al., 2007; Smith, 2009). In cattle, the classical presentation of infection is woody tongue, but also soft tissues like lymph nodes (retropharyngeal and submandibular) and other tissues of the head, pharynx, chest, flank, stomach, omentum and limbs can be affected (Radostits et al., 2007; Taghipour-Bazargani et al., 2010). Grossly, Actinobacillosis is characterized by the presence of granulomas with purulent discharges characteristically containing ‘sulphur’ granules. Microscopically, pyogranulomas with Splendore-Hoepelli phenomenon surrounded by fibrosis after acute local inflammation are the most common features. The present case describes the clinical manifestations, bacteriologic, gross and histo-pathologic characteristics of an unusual manifestation of actinobacillosis in a cow.